2000
DOI: 10.2105/ajph.90.3.360
|View full text |Cite
|
Sign up to set email alerts
|

The dynamics of alcohol and marijuana initiation: patterns and predictors of first use in adolescence

Abstract: A B S T R A C TObjectives. This study, guided by the social development model, examined the dynamic patterns and predictors of alcohol and marijuana use onset.Methods. Survival analysis and complementary log-log regression were used to model hazard rates and etiology of initiation with time-varying covariates. The sample was derived from a longitudinal study of 808 youth interviewed annually from 10 to 16 years of age and at 18 years of age.Results. Alcohol initiation rose steeply up to the age of 13 years and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
86
1
7

Year Published

2003
2003
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(108 citation statements)
references
References 37 publications
11
86
1
7
Order By: Relevance
“…The finding is comparable to another study 7 that found 37.1% lifetime prevalence among the general public. The findings of high levels of drug use among PWDs support the notion by researchers 11,12 that PWDs are at a high risk of substance use due to myriad of factors including stigma, discrimination, health problems, alienation by society, and a lack of access to adequate and appropriate treatment services, among others. These findings also support those of another researcher 13 who found that PWDs report higher incidence rates of Alcohol, Tobacco, and Other Drug (ATOD) use than their peers.…”
Section: Figure 1 Ages At First Use Of Drug/s Discussionsupporting
confidence: 77%
“…The finding is comparable to another study 7 that found 37.1% lifetime prevalence among the general public. The findings of high levels of drug use among PWDs support the notion by researchers 11,12 that PWDs are at a high risk of substance use due to myriad of factors including stigma, discrimination, health problems, alienation by society, and a lack of access to adequate and appropriate treatment services, among others. These findings also support those of another researcher 13 who found that PWDs report higher incidence rates of Alcohol, Tobacco, and Other Drug (ATOD) use than their peers.…”
Section: Figure 1 Ages At First Use Of Drug/s Discussionsupporting
confidence: 77%
“…Strong parental norms against teenage drinking and communication of parental disapproval of drinking have also been shown to reduce the risk of initiation in early adolescence 40 and have been linked to less peer influence to use alcohol, greater self-efficacy to refuse alcohol, and lower frequency of alcohol use behavior. 32 Similarly, national data demonstrate that adolescents who believe that their parents would strongly disapprove of them using substances are significantly less likely to use that substance than adolescents whose parents only somewhat disapproved.…”
Section: Family Factors Affecting Adolescent Substance Usementioning
confidence: 99%
“…Social influences such as those related to parenting, peer group, and neighborhood on use of any specific substance in adolescence often overlap with those for use of other substances and for the general category of problem behaviors (Dishion and Patterson, 2006; Hicks et al, 2004). Additionally, polysubstance use is common in adolescence (Leatherdale et al, 2009), and onset of one kind of substance use hastens onset of others (Kosterman et al, 2000). Thus, models of risk for marijuana use onset should accommodate the likelihood that some risks tend to be generalized rather than substance specific.…”
Section: Introductionmentioning
confidence: 99%